Monk and Canon: Some Patterns in the Religious Life of the Twelfth Century - Brooke, Christopher Nugent Lawrence (Studies in church history, 1985)
If you were a religious of the i ith or 12th centuries choosing the order in which you were to find your vocation, how did you distinguish order from order, monk from canon? How did you determine gradations of the ascetic life? If you were a founder or benefactor, planning to found a new religious house, how did you determine which order to favour? At a time when asceticism and the religious orders flourished as never before, choice must have been bewildering. There is a copious contemporary literature arguing the relative merits of this mode and that; and modern scholars have offered a remarkably wide variety of advice. Some have proceeded on the assumption that there must have been a fundamental difference and have pursued it as best they might; others, disappointed in the chase, have doubted if any true difference existed. Some have seen all such differences engulfed in the deeper stream of new impulses and modes which affected every approach to the religious life in this age; others have said that to lose track of such differences is to take a very superficial view of the meaning of the rules of St Augustine and St Benedict. It is very easy indeed to take an entirely sceptical view; and I propose to start by stating the case for saying there was no difference visible to all in every part of Europe - that no general statement of the difference stands up to close inspection. But to rest the matter there, I am sure, would be superficial and mistaken - and so in the second part of this paper I embark on the much more hazardous path of determining where the difference lay. I shall try not to add another definition to the scrap heap, but to show by looking at a number of local situations how it might have appeared both externally to a founder and at a deeper level to an educated man with some discernment of different approaches to the ascetic life and religious spirituality. Yet the ultimate abiding impression is of the strangeness of the central fact: at a time when men were seeking their own religious vocation in numbers never before approached in medieval Europe - and patrons lavishing resources on an unparalleled variety of new religious houses - it is especially difficult for us to observe in many cases where the differences lay.